Pemikiran islah Yusuf Ahmad Lubis - Khairuddin Said. (Penerbit Universiti Malaya, 2012)
Biography of Yusuf Ahmad Lubis, an ulama from Sumatera Utara, and his thoughts on Islamic renewal in Indonesia and Malaysia.